Conceptualizing caregiver workload: an exploratory study guided by NASA TLX. (November 2019) - Rutkowski, R.A.; Ponnala, S.; Gonzalez-Vargas, J.; Gilmore-Bykovskyi, A.; Block, L.; Kind, A.J.; Werner, N.E.
Persons with dementia (PwD) are heavily dependent on the support of informal, dementia caregivers to fulfill their day-to-day care needs. Dementia caregivers, often friends and family members of the PwD, are unpaid, non-professional individuals who take on many of the care responsibilities. Due to the lack of formal training, social support, and information resources, among other factors, dementia caregivers are often at risk for negative outcomes such as stress and burden. There have not been any comprehensive assessment tools to predict these negative outcomes. Therefore, we employ the NASA TLX dimensions to conceptualize caregiver workload. This study operationalizes the NASA TLX dimensions in the context of dementia caregiving and illustrates examples for each of the dimensions. The results indicate that the NASA TLX does not include all of the factors necessary to conceptualize caregiver workload and prescribe a need for developing a robust caregiver workload assessment tool.